Ultra-stable sub-meV monochromator for hard X-rays - Toellner, T S (Journal of synchrotron radiation, 2015)
A high-resolution silicon monochromator suitable for 21.541 keV synchrotron radiation is presented that produces a bandwidth of 0.27 meV. The operating energy corresponds to a nuclear transition in (151)Eu. The first-of-its-kind, fully cryogenic design achieves an energy-alignment stability of 0.017 meV r.m.s. per day, or a 100-fold improvement over other meV-monochromators, and can tolerate higher X-ray power loads than room-temperature designs of comparable resolution. This offers the potential for significantly more accurate measurements of lattice excitation energies using nuclear resonant vibrational spectroscopy if combined with accurate energy calibration using, for example, high-speed Doppler shifting. The design of the monochromator along with its performance and impact on transmitted beam properties are presented